Determinação da pena privativa de liberdade: circunstâncias judiciais subjetivas - Fuller, Paulo Henrique Aranda (2010)
This paper tries to analyze the legal circumstances of a subjective nature - culpability, history, social behavior, agent s personality and motives of the crime - that occupy a central position in determining the sentence (cognitive judicial individualization), directing the court decision on the kind of penalty in case of alternative commination - the quantification of the base penalty, the initial regime s determination of the performance of the liberty s private penalty, the sufficiency of its replacement, the exasperation in particular continuing offense, the possibility of probation, criminal transaction and conditional suspension of the process. The indeterminacy of concepts, the shallowness of cognition and the absence of judicial reasoning properly about these conditions can transform the discretion legally bound to unwanted arbitrariness or absolute decisionism. The culpability, in its meaning of the penalty s amount, performs different functions and may act as the upper limit of the penalty (proportionality to the unjust criminal and legal ward) and as a judicial circumstance (individualization of the defendant s personal conditions). As the upper limit of the penalty, the culpability represents assurance (limiting retributive function as the ruling purpose of the penalty) in the face of preventive circumstance - general and specific, positive and negative. As a judicial fact, it allows the individual measurement of the unjust level of consciousness and of the diverse behavior chargeability s degree and of the subject s internal participation. We argue that the judicial circumstances imply the discretion in the penalty s determination, which must be controlled by defining its limits and cognitive materials (fission of the instruction and trial: interlocutory of the penalty s culpability and determination)